Undervaluation through Foreign Reserve Accumulation : Static Losses, Dynamic Gains - Korinek, Anton; Servén, Luis (Washington, DC: World Bank, 2012)
This paper shows that real exchange rate undervaluation through the accumulation of foreign reserves may improve welfare in economies with learning-by-investing externalities that arise disproportionately from the tradable sector. In the presence of targeting problems or when policy choices are restricted by multilateral agreements, first-best policies such as subsidies to capital accumulation, or subsidies to tradable production are not feasible. A neo-mercantilist policy of foreign reserve accumulation "outsources" the targeting problem or overcomes the multilateral restrictions by providing loans to foreigners that can only be used to buy up domestic tradable goods. This raises the relative price of tradable versus non-tradable goods (i.e. undervalues the real exchange rate) at the static cost of temporarily reducing tradable absorption in the domestic economy. However, since the tradable sector generates greater learning-by-investing externalities, it leads to dynamic gains in the form of higher growth. The net welfare effects of reserve accumulation depend on the balance between the static losses from lower tradable absorption versus the dynamic gains from higher growth.